Implementation of Character Education in Madrasah Students - Daryaman, Daryaman; Mayasari , Annisa; Supriadi, Deni; Wahyu Hoerudin , Cecep; Susandi , Ari (International Journal of Education and Digital Learning (IJEDL), 2024)
The background to this research is the importance of education and character development in students. Problems related to deviations that are far from noble character very often occur in today's young generation. Character education is the initial foundation for instilling character in students so that they become a generation with noble morals. The aim of this research is to determine the implementation of character education in Private Madrasah Tsanawiyah. A qualitative method with a descriptive approach was used in this research, data analysis and examination was carried out by comparing data from several sources and then drawing conclusions. The results of the research show that the strategies implemented by the school have an impact on changing students' attitudes and behavior towards a better direction by reflecting noble character values, such as: religious, honest, tolerant, disciplined, love of the country, friendly/communicative, caring. environment, and responsibility. This is carried out by the entire school community with an Islamic character culture which is the hallmark of Madrasah Tsanawiyah.